World food price bubble and China's food security - You, Liangzhi (2009)
The price of nearly every agricultural commodity sharply increased in 2008, creating a global food price bubble. At their peaks in the second quarter of 2008, world prices of wheat and maize were three times higher than at the beginning of 2003, and the price of rice was five times higher (Figure 1-3). The surge in food prices has become a major political concern because of its role for inflation, its impacts on the whole economy, and because of adverse effects on the wage earning poor and middle class. The price developments can help reduce urban – rural income gaps in the aggregate, but some groups in rural areas lose and others gain. The issue is not only one of too fast increases in prices, but one of risky volatility and of inappropriate policy responses around the world posing threats for free trade and possibly for political stability in some countries. In China, Consumer Price Index (CPI) kept increasing in 2008. CPI increased 8.5% in April 2008, a monthly record in 12 years. The increases from food, vegetable, livestock prices are the main reasons behind the CPI increase.